Effect of complexation with lanthanide metal ions on the photochromism of (1,3,3-trimethyl- 5 ′ -hydroxy- 6 ′ -formyl- indoline-spiro2,2 ′ -[2h]chromene) in different media (International Journal of Photoenergy)
Complexation of lanthanide ions {Ln(III) ions [Tb(III), Eu(III), or Sm(III)]} with the spiropyran-derived merocyanine obtained in dark and under steady irradiation of indoline spiropyran (1,3,3-trimethyl- 5 ′ -hydroxy- 6 ′ -formyl-indoline-spiro-2,2 ′ -[2H]chromene) induces a noticeable hypsochromic shift of about 10–110 nm of its visible absorption band concomitant with hypochromic effect and influences its thermal bleaching in the dark. The effect of lanthanide ions and medium on photochromic, spectral-and-kinetic, and luminescence properties of the spiropyran and its complexes in solution and polymer matrix of polymethylmethacrylate (PMMA) is studied. Efficient energy transfer from the spiropyran moiety results in efficient typical luminescence from the Ln(III) ion that becomes more pronounced in polar nonalcoholic solvents and PMMA solid matrix. Moreover, luminescence mappings for pattern recognition analysis have been obtained from which the nature of the solvent and/or the ligand is clearly identified.